2003
DOI: 10.1128/mcb.23.23.8862-8877.2003
|View full text |Cite
|
Sign up to set email alerts
|

mTOR-Dependent Regulation of Ribosomal Gene Transcription Requires S6K1 and Is Mediated by Phosphorylation of the Carboxy-Terminal Activation Domain of the Nucleolar Transcription Factor UBF†

Abstract: Mammalian target of rapamycin (mTOR) is a key regulator of cell growth acting via two independent targets, ribosomal protein S6 kinase 1 (S6K1) and 4EBP1. While each is known to regulate translational efficiency, the mechanism by which they control cell growth remains unclear. In addition to increased initiation of translation, the accelerated synthesis and accumulation of ribosomes are fundamental for efficient cell growth and proliferation. Using the mTOR inhibitor rapamycin, we show that mTOR is required fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
337
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(350 citation statements)
references
References 68 publications
11
337
0
2
Order By: Relevance
“…It is interesting to mention in this context that a recent microarray analysis has also shown that DN-HNF1A expression decreases the transcription of several ribosomal proteins [34]. Targets of S6K1 other than ribosomal protein S6 have been identified, such as the transcription factor cAMP responsive element modulator (CREM)-τ, the RNA splicing/export factor cap binding protein 80 (CBP80) and the eukaryotic translation elongation factor 2 (eEF2) [35], which may mediate additional activities of S6K1 that were hitherto partially unknown. Loss of S6k1 in Drosophila is semi-lethal, and a markedly reduced body size was seen in the surviving adults [36].…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to mention in this context that a recent microarray analysis has also shown that DN-HNF1A expression decreases the transcription of several ribosomal proteins [34]. Targets of S6K1 other than ribosomal protein S6 have been identified, such as the transcription factor cAMP responsive element modulator (CREM)-τ, the RNA splicing/export factor cap binding protein 80 (CBP80) and the eukaryotic translation elongation factor 2 (eEF2) [35], which may mediate additional activities of S6K1 that were hitherto partially unknown. Loss of S6k1 in Drosophila is semi-lethal, and a markedly reduced body size was seen in the surviving adults [36].…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrated that a downregulation of rRNA synthesis induced by silencing the POLR1A gene coding for the RNA polymerase I catalytic subunit stabilised p53 without giving rise either to structural changes in the nucleolar components or leakage of the nucleolar proteins to the nucleoplasm. As we found that, according to the available evidence (see reviews by Zhang and Lu, 2009;Deisenroth and Zhang, 2010), the inhibition of the synthesis of rRNA was associated with an increased binding of rpL5 and rpL11 to MDM2, we investigated whether p53 stabilisation also occurred in experimental models in which the synthesis of rRNA and ribosomal proteins was reduced at the same time, such as in cells after serum deprivation or exposure to rapamycin (O'Mahony et al, 1992;Mahajan, 1994;Glibetic et al, 1995;Hannan et al, 2003;Caldarola et al, 2004;Gera et al, 2004;Bilanges et al, 2007). The data obtained, showing no p53 stabilisation in either conditions, indicated that p53 was stabilised only when the reduction of rRNA synthesis was not accompanied by a similar variation in the synthesis of ribosomal proteins, that is, when a relative increase in ribosomal protein availability for MDM2 binding was induced.…”
Section: Introductionmentioning
confidence: 99%
“…Once the on/off decision has been made, eukaryotic cells then appear to regulate the frequency at which RNA polymerase I initiates on each active gene in order to fine-tune the amount of rRNA produced. Studies in yeast and mammals indicate that fine-tuning is accomplished primarily through signal transduction mechanisms that lead to the post-translational modification of essential RNA polymerase I transcription factors [57][58][59][60][61][62].…”
Section: Rrna Gene Dosage Control Mechanisms and The Mammalian Norc Cmentioning
confidence: 99%